Development of Online Crossword Puzzles as A Media of Learning on Hydrocarbon Material 11th Grade Senior High School - Syaza P Dinanti; Suryelita Suryelita (Universitas Negeri Padang, 2023)
Hydrocarbons are a fairly dense material, it is necessary to strengthen the concept of this material in the form of exercises. As a result of the distribution of the questionnaire, 98% of students participated in training in the form of a game. One game that can be used as practice is a crossword puzzle. This study aims to produce an online crossword game and determine its validity and level of practicality. The research method used is research of development with a plomp model. The research time was carried out from January 2021 to October 2022. The place where this research was carried out was the FMIPA UNP campus and schools. The results of the study found that the crossword game media obtained an Aiken V index value at construct validation of 0.87 and content validation of 0.91. Furthermore, the results of the small group practicality test showed that the resulting media received a percentage score of 83% teacher response and 86% student response. This study concludes that the online crossword game media developed is already valid and very practical.